THE INFLUENCE OF MICRONUTRIENT DEFICIENCY AND GUT MICROBIOTA ON IMMUNE RESPONSE: THE ROLE OF MICROBIOTA AND ITS METABOLITES (International journal of artificial intelligence, 2026)
Micronutrients are substances necessary for the normal functioning of the body. An important component of the body’s defense system is a healthy gut microbiota. This article reviews current scientific approaches to correcting micronutrient deficiency and modulating the microbiota to improve the functional state of the immune system in children and adolescents, using the examples of Multi-Tabs® vitamin-mineral complexes and Bifiform® probiotics.